Dampak Program Coorporate Social Responbility (CSR) PT Pertamina Persero Unit Padang Bagi Masyarakat Dikelurahan Air Manis Kota Padang - Rivonny, Balqis (journal of residu, 2019)
The Corporate Social Responsibility (CSR) program is a program provided by a company as a form of corporate social responsibility to the community around the company. The Guidelines for Corporate Social Responsibility (CSR) are contained in the Law Number. 40 of 2007 contained in Article 1 concerning Limited Liability Companies. PT Pertamina Persero Unit Padang as the company runs this Corporate Social Responsibility program in Air Manis Village, Padang City in the form of providing clean water facilities and providing sanitation facilities for the community. After the implementation of the Corporate Social Responsibility program there are several problems that arise such as clean water facilities that do not flow so that the community cannot access clean water and the level of community participation is lacking. This research was conducted to find out how the impact of the Corporate Social Responsibility program was directly felt by the community in Air Manis Village, Padang City through 3 impact indicators in the form of social change impacts, health impacts, environmental impacts and conflicts, constraints contained in this CSR program and efforts done in overcoming existing. This study uses descriptive qualitative. The research informant technique used purposive sampling. Data collection techniques in the form of observation, interviews and documentation. Based on the results of the interview, the impact of the Corporate Social Responsibility program gives many benefits to the community. The perceived impact is that people have more awareness to always live healthier and always maintain the environment starting from the use of clean water and always defecating in healthy latrines and the level of public health cases is low but over the past few months the Coorporate Social Responsibility program is no longer felt by benefits because water that does not flow in the clean water supply is provided. Keywords: impact, corporate social responsibility, society